(untitled) (Eurasian Medical Research Periodical, 2021)
The article presents the study of milk productivity of karakul sheep depending on the colour in the northern conditions of the Republic of Karakalpakstan. Optimal opportunities of increasing Milk productivity were determined; the results of changing daily milk productivity in agedependent dynamics were given.